1978
DOI: 10.1136/bmj.1.6126.1518
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic-uraemic syndrome complicating shigella dystentery in south Indian children.

Abstract: The infants of mothers with skinfold thicknesses less than 7 mm (less than 25th percentile for the whole group) had significantly smaller anthropometric measurements than those of mothers with skinfold thicknesses greater than 12-1 mm (greater than 75th percentile) (see table II).There were significant differences between the paying and nonpaying groups in infant weight and length and maternal height and triceps skinfold thickness (see table III). Infants weighing under 2500 g constituted 24 % of the whole gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 14 publications
(1 reference statement)
1
36
1
Order By: Relevance
“…We have previously demonstrated that platelet function is impaired in a modified model of the MGSR (14). This model which has similar features to the form of HUS associated with shigellosis (5,8) has been studied extensively in our laboratory (14). The purpose of the present study was to determine whether circulating neutrophils were functionally impaired as a result of prolonged infusion of endotoxin in this model.…”
mentioning
confidence: 99%
“…We have previously demonstrated that platelet function is impaired in a modified model of the MGSR (14). This model which has similar features to the form of HUS associated with shigellosis (5,8) has been studied extensively in our laboratory (14). The purpose of the present study was to determine whether circulating neutrophils were functionally impaired as a result of prolonged infusion of endotoxin in this model.…”
mentioning
confidence: 99%
“…Within the genus of Shigella, Shigella dysenteriae type 1 (Shiga's Bacillus) causes both endemic and epidemic shigellosis with serious extraintestinal complications, including the hemolytic uremic syndrome, accompanied by a high rate of mortality: Today the organism manifests almost universal antibiotic resistance (2)(3)(4)(5)(6)(7). In addition, S. dysenteriae type 1 is unique among shigellae in that it alone expresses an exotoxin called Shiga toxin.…”
mentioning
confidence: 99%
“…HUS has been reported to be a frequent complication during such outbreaks, with an incidence ranging from 14 out of 91 cases to almost one-third of cases (Oneko et al, 2001;Nathoo et al, 1998). HUS following shigellosis appears to be a much more aggressive and severe disease than HUS due to enterohaemorrhagic E. coli because of severe renal involvement with prolonged oliguria (Bhimma et al, 1997;Raghupathy et al, 1978;Koster et al, 1984;Bhuyan et al, 1985). The reported mortality (range 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Europe and Americas have documented evidence of STEC infections in 33-60 % of patients with HUS (Karmali et al, 1983;Scotland et al, 1988;Lopez et al, 1989). However, in South-East Asia and Africa, HUS has been related to epidemics of S. dysenteriae type 1 (Raghupathy et al, 1978;Nathoo et al, 1995;Bhimma et increase in incidence of HUS has been reported that coincided with an epidemic of S. dysenteriae 1 (Rollins et al, 1995). HUS has been reported to be a frequent complication during such outbreaks, with an incidence ranging from 14 out of 91 cases to almost one-third of cases (Oneko et al, 2001;Nathoo et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation